PPP2R5D-Related Neurodevelopmental Disorder or Developmental and Epileptic Encephalopathy?: A Novel Phenotypic Description and Review of Published Cases - Madaan, Priyanka; Kaur, Amrit; Saini, Lokesh; Paria, Pradip; Vyas, Sameer; Sharma, Amit R.; Sahu, Jitendra K. (Neuropediatrics, 2021)
Background Protein phosphatase 2 regulatory subunit B′ delta (PPP2R5D)-related neurodevelopmental disorder is caused by pathogenic variations in the PPP2R5D gene, product of which is involved in dephosphorylation. This is a rare disorder with description limited to case reports. Its phenotypic spectrum has expanded over the last decade.Methods We report a child with a developmental and epileptic encephalopathy phenotype with a pathogenic PPP2R5D variant. This phenotype has not been previously reported. We also reviewed the previously published reports of patients with this disorder.Results Including the index child, 28 cases (15 girls) were identified from nine relevant research items for analysis. All patients had developmental delay. History of seizures was observed in seven patients while macrocephaly was seen in nearly 80% of patients. Nonneurological manifestations were observed in 13 patients with the most common one being ophthalmological manifestations. The most common genetic variation was c.G592A (p.E198K). The common phenotypic associations of this variation were developmental delay, macrocephaly (11/15), and epilepsy (6/15).Conclusion PPP2R5D gene variations should be suspected in children with developmental delay, autistic features, macrocephaly with or without epilepsy in the absence of any clear etiology. Dysmorphic features might provide a diagnostic clue. DEE phenotype may also be the presenting feature and might be an underreported entity.
Keywords: PPP2R5D; epilepsy; DEE; neurodevelopmental disorder